STABILITY OF AN ELASTIC ROD WITH DYNAMIC ABSORBERS UNDER HARMONIC TRANSVERSE VIBRATIONS - Anvar Kudratov; Shokhzod Khamitov (World Scientific Research Journal, 2025)
Abstract. This paper considers the stability problem of a simply supported rod with two dynamic vibration absorbers and hysteretic energy dissipation. Linearization of dependencies describing hysteretic energy dissipation due to imperfect elasticity of the material is carried out using Pisarenko-Boginich functional in a frequency-independent form